A separação dos poderes e os freios e contrapeso na Constituição de 1988: a atuação do Poder Judiciário - Camargo, Beatriz Meneghel Chagas (2017)
The present study aimed to analyze whether the checks and balances in the Federal Constitution of 1988 ensure the balance between the Executive, Legislative and Judicial Powers. The separation of powers and the mechanisms of checks and balances were conceived with the intention of, in containing the abuse of the holders of the powers, to guarantee the fundamental rights of the individuals. The question that arises in this study is whether the way in which such instruments of mutual control are distributed among the three Powers, in the Federal Constitution of 1988, responds to the current Brazilian reality, in which the Judiciary has been gaining a prominent position